9-Aminoacridin-10-ium 4-aminobenzoate dihydrate - Dhanabalan, Nallathambi; Thanigaimani, Kaliyaperumal; Arshad, Suhana; Razak, Ibrahim Abdul; Santhanaraj, K. Joseph (International Union of Crystallography, 2014)
The asymmetric unit of the title hydrated salt, C13H11N2 +.-C7H6NO2-.2H2O, consists of two independent 9-aminoacridinium cations, two 4-aminobenzoate anions and four water molecules. Both 9-aminoacridinium cations are essentially planar, with maximum deviations of 0.034 (1) and 0.025 (2) A ° , and are protonated at the pyridine N atoms. The 4-aminobenzoate anions are approximately planar, with dihedral angles of 9.16 (19) and 5.4 (2)° between the benzene ring and the carboxylate group. In the crystal, the two independent anions are connected by N—H...O hydrogen bonds, forming a layer parallel to (100). The layers are connected through the cations by N—H...N and N—H...O hydrogen bonds. The water molecules, which form O—H...O hydrogen-bonded chains along the b-axis direction, connect the anions and the cations by O—H...O, N—H...O and C— H...O hydrogen bonds. The crystal structure also features n–n interactions [centroid–centroid distances = 3.6343 (9)– 3.8366 (10) A °] and a C—H...n interaction.